The Masculine Modern Woman - Ingemarsdotter, Jenny, author.
1 online resource (264 pages)
Keywords: This book takes a fresh approach to one of the most popular cultural symbols of modernity in the 1920s—the "masculine" modern woman. Uncovering discourses on female masculinity in interwar Sweden, a nation that struggled to become modern but not decadent, this study examines cultural representations and debates across several arenas including fashion, film, sports, automobility, medicine and literature. Drawing on rich empirical material, this book traces not only how the masculine modern woman reshaped the imaginary space of what women could be, do and desire, but also how this space was eventually shrunk in order to fit into an emerging vision of a family-oriented "people’s home."